Sensory processing of children and students with autism spectrum disorder and typical development in relation to gender and age - Roknić Ana T. (Univerzitet u Beogradu - Fakultet za specijalnu edukaciju i rehabilitaciju, 2021)
Introduction. Sensory processing is a neurobiological process in which a person uses their senses, sends information to an appropriate reception and processing center, and responds to environmental stimulations. Previous research has shown that sensory processing difficulties are more common among people with autism spectrum disorder than among people of the typical population. Objectives. The aim of this paper was to determine the patterns of sensory processing in subjects of the typical population and subjects with autism spectrum disorder, as well as gender and age differences in sensory profiles in these groups of subjects. Methods. Using The Child Sensory Profile 2 as the measuring instrument, the characteristics of sensory processing were examined in 120 subjects of both genders, 60 subjects with autism spectrum disorder and 60 subjects of typical development, ages three to 13 years and 11 months. Results. The obtained results show that there are differences between the two groups of respondents and that these differences occur in all nine subscales of the instrument. It was found that subjects with autismspectrumdisorder hadmore difficulty in processing sensory information compared to subjects of the typical population, especially in the domain of tactile perception. The results also show that the quality of sensory information processing in both groups of respondents improved with age. In relation to the respondents' gender, the obtained differences were significant in the domain of the total score of the instrument, in favor of the boys, but this was not observed in the measurements on all subscales. Conclusion. In accordance with the above findings, when creating an individual educational plan, it is necessary to take into account all the specifics of sensory processing of children with autism spectrum disorder.